From the South Seas to Soho Square: Joseph Banks's Library, collection and Kingdom of natural history. (5th June 2019) - Rose, Edwin D.
Abstract : The library and herbarium of Joseph Banks was one of the most prominent natural history collections of late eighteenth-century Britain. The examination of the working practices used in Banks's library, which was based at 32 Soho Square from 1777, reveals the activities of the numerous individuals who worked for Banks and on his collections from the early 1770s until 1820. Banks's librarians and their assistants used a range of paper technologies to classify and catalogue the vast numbers of new botanical species being discovered at this time. These practices of managing information changed as the decades progressed, reflecting the changes to systems of classification and the different research projects of Banks and his natural history staff. Banks's great wealth and powerful position as President of the Royal Society gave him the means to build and use this rigorously organized collection and library to influence a range of other private and institutional collections for almost 50 years.